Is De-escalated Bisphosphonates Therapy a Suitable Alternative to Standard Dosing in Malignant Tumor Patients With Bone Metastases: A Systematic Review and Meta-Analysis - Luo, Qiuhua; Men, Peng; Liu, Zhiyong; Zhai, Suodi; Jiang, Mingyan (Frontiers in Oncology, 2019)
Background: Previous studies have preliminarily identified the non-inferior efficacy for reducing skeletal-related event (SRE) rates between de-escalated (Q12w) and standard (Q3-4w) bone-targeting agents therapy in malignant tumor patients with bone metastases. In this study, we aim to make further efforts to analyze whether the de-escalated bisphosphonates (BPs) strategy is a suitable option by comprehensively retrieving and synthesizing state-of-the-art evidence. Methods: An extensive electronic search for randomized controlled trials (RCTs) comparing a BPs standard strategy with de-escalated one in patients with bone metastases was performed up to June 2018. Outcomes of interest were general and individual types of SRE, skeletal morbidity rate (SMR), bone pain, bone turnover biomarkers and adverse events (AEs). Continuous and dichotomous outcomes were summarized by the weighted mean difference (WMD) and risk ratio (RR) respectively, with 95% confidence intervals (CIs). Results: A total of eight studies representing six unique trials (involving 3114 patients) were included. Pooled results indicated comparable efficacy on general SRE (RR 0.99, 95% CI 0.87-1.12; P = 0.86; I2 = 0%) and SMR (WMD 0.00, 95% CI -0.02-0.03; P = 0.81; I2 = 0%). However, the rate of surgery involving bones was significantly higher in de-escalated group than standard group (RR 1.92, 95% CI 1.17-3.15; P = 0.01; I2 = 0%) among individual types of SRE. Several trials also demonstrated increased levels of C-terminal or N-terminal telopeptide in de-escalated group. Meta-analyses for gastrointestinal disorders, dizziness and back pain showed significant reductions by 27% (RR 0.73, 95% CI 0.57-0.94; P = 0.01; I2 = 0%), 48% (RR 0.52 95% CI 0.32-0.86; P = 0.01; I2 = 0%) and 29% (RR 0.71, 0.51-0.99; P = 0.04; I2 = 0%), respectively, compared to the standard therapy. Conclusion: For malignant tumor patients with bone metastases, a de-escalated BPs strategy is proved to have a better safety profile compared to standard dosing. Although the efficacy is generally comparable on SRE and SMR between the two dosing regimens, trials with long duration and large sample sizes are still warranted to make a solid judgment.